The Effect of High Intensity Interval Training (HIIT) Training Method Using Elevation Training Mask (ETM) on Anaerobic Capacity - Nurjaya, Dede Rohmat; Septina, Trisha Aryanti; Purnamasari, Ira; Wibowo, Ricky (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine the effect of the high-intensity interval training method using an elevation training mask on anaerobic capacity. This research uses an experimental method of One-Group Pretest-Posttest Design. The sample consisted of 10 student-level athletes in one of the women's futsal clubs. The test instrument used was the running-based anaerobic sprint test—data analysis using non-parametric statistics. The results showed that the paired-sample t-test had a sig value. Of 0.016 so it can be concluded that there is an effect of high-intensity interval training using an elevation training mask on the increase in anaerobic capacity.